Socio-economic conditions of workers of stone crushing area in Sonbhadra district: A study in health geography - Shailesh Kumar; G. N. Srivastava; A. P. Mishra (National Geographical Journal of India, 2025)
Socio-economic status refers to an individual’s position within society and is determined by factors such as income, occupation, education, wealth, and social class. It serves as an indicator of an individual’s or group’s standing in the community and reflects overall quality of life. In the Indian context, however, socio-economic status is strongly influenced by caste identity, which often regulates access to power, privilege, and resources. The present study aims to examine the extent and intensity of pollution caused by dust emissions from stone crushing units and their impact on workers as well as households in nearby areas. Although the dispersion and intensity of dust generated by these units may differ from that produced by large-scale industries, it nonetheless poses significant environmental and health concerns. The findings reveal limited awareness and poor hygienic practices among the respondents. Out of 240 respondents, a majority (74.58 per cent) were unaware of the concept of scientific sanitation, while only 25.42 per cent reported having such knowledge. Similarly, 64.17 per cent of respondents did not wash their hands before meals, whereas 35.83 per cent practiced handwashing prior to eating. A large proportion of respondents (75.42 per cent) consumed their lunch within dusty stone-crushing sites, while only 24.58 per cent avoided eating in such environments. Participation in health camps was also notably low, with 70 per cent of respondents reporting non-participation, compared to 30 per cent who had attended health camps. These findings highlight the intersection of socio-economic constraints, occupational exposure, and limited health awareness, underscoring the need for targeted interventions to improve sanitation practices, occupational health, and overall well-being among stone crusher workers and surrounding communities.